Development of Local Potential Handouts as SDGs-based Teaching Materials to Enhance Critical Thinking - Romadhan, Siddik; Fajarianingtyas, Dyah Ayu; Hidayat, Jefri Nur; Matlubah, Helliyatul (STAI Hubbulwathan Duri, 2024)
Critical thinking is an active process because it involves question and answer activities. This skill is important for students to have as one of the 21st Century skills that can support the achievement of Sustainable Development Goals (SDG's). The objectives of this world program need to be instilled from an early age so that students have an attitude of concern for environmental sustainability. The importance of understanding the SDGs can be taught in schools. The problem raised focuses on the unavailability of handouts that integrate local potential in science material and explore student activities in critical thinking as one of the skills of the 21st century. The role of this teaching material can be to train critical thinking skills in learning to achieve the SDGs goal of protecting terrestrial ecosystems. The aim of the research is to produce a handout on the local potential of the SDGs and determine whether there is an increase in students' critical thinking after using the handout. The method used by Research and Development (RD) refers to 4D. Critical thinking data measured from description tests were obtained before and after the treatment designed to include students' abilities in providing explanations, building skills, designing strategies and tactics, explaining further and concluding. The results of the research show an increase in critical thinking skills of 0.60 as indicated by the N-gain and positive student responses after using the development product. These results are in line with the research objective of integrating SDGS-oriented local potential into teaching materials. The involvement of a teacher in designing teaching materials containing local SDGs-oriented potential is very necessary as one of the efforts that can be carried out in the education sector. Conclusion the science learning process on plant structure material and its use in technology was effective after using the SDGs-based local potential handout.